Beauty Without Consequence: A Reflection of Late-Victorian Upper-Class Privilege in the Picture of Dorian Gray By Oscar Wilde - Yosep B Margono Slamet; Maria Febrianti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This paper examines how The Picture Dorian Gray by Oscar Wilde marks a critical turn in which he critiques late-Victorian upper-class privilege and moral immunity. While previous scholarship has predominantly analyzed the novel as a moral allegory or aesthetic treatise, this study employs cultural materialism as a theoretical framework to demonstrate how Wilde uses Dorian’s isolation of his portrait and subsequent hedonistic experimentation as symbolic representations of the aristocracy’s ability to shield him from moral and social consequences. Wilde’s text reveals how the English aristocracy could embody ideals of beauty and reap princely treatment while committing debauchery without reproach. Through Culler’s close reading method toward this novel, especially chapters eight and nine, this analysis reveals how Dorian’s act of hiding the portrait symbolizes social denial, while his obsessive aesthetic consumption reflects the practices of the leisure class. This shows that Wilde hints Dorian’s social circle accepts his sensual life simply because his appearance remains unmarred–a commentary on class privilege. By examining the specific textual elements and historical context of—especially—chapters eight and nine of this novel, this study contributes to the understanding of how Wilde’s novel serves as both a product of and commentary on the class structures and moral hypocrisy of late-Victorian England.